2018
DOI: 10.3389/fmed.2018.00074
|View full text |Cite
|
Sign up to set email alerts
|

An Original Approach to Evaluating the Quality of Blood Donor Selection: Checking Donor Questionnaires and Analyzing Donor Deferral Rate

Abstract: Blood donor selection is a cornerstone for blood transfusion safety, designed to safeguard the health of both donors and recipients. In the Service du Sang, Belgian Red Cross, French and German-speaking part of Belgium (SFS), health professionals (HPs) are allowed to interview donors on their own after formal qualification. This qualification is afterward evaluated by means of two complementary quality indicators: monitoring of donor health questionnaires (DHQs) and analysis of donor deferral rate. The study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…To our knowledge, this study represents the first large‐scale review of donor deferral and return patterns in the South African setting. We confirmed that almost one in five (17·2%) donors who presented for donation were deferred, which decreased to 15·6% in 2019, but remained higher than published blood donor deferral levels of 12–13% in Western and other developing countries [4–9]. Deferral patterns differed significantly by gender, population group, age, geographical region as well as donor and clinic type; almost half of all deferrals were for Out of Range Hb.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…To our knowledge, this study represents the first large‐scale review of donor deferral and return patterns in the South African setting. We confirmed that almost one in five (17·2%) donors who presented for donation were deferred, which decreased to 15·6% in 2019, but remained higher than published blood donor deferral levels of 12–13% in Western and other developing countries [4–9]. Deferral patterns differed significantly by gender, population group, age, geographical region as well as donor and clinic type; almost half of all deferrals were for Out of Range Hb.…”
Section: Discussionsupporting
confidence: 72%
“…The World Health Organization (WHO) recommends the collection and regular review of data on donor deferrals by BTS to assess the major causes of deferral, in particular those indications that result in the greatest numbers of donor deferrals and those presenting high risk to patients [1]. While donor deferral rates of 12-13% are comparable between Western [4,5] and developing countries [6][7][8][9], blood donor behaviour patterns and transfusion transmissible infection (TTI) prevalence vary from region to region. It is therefore imperative to gather and analyse country-specific data.…”
Section: Introductionmentioning
confidence: 99%
“…The deferral can be temporary or permanent depending upon the underlying condition. In our study, we aimed to find the frequency and common causes of deferrals among the blood donors [11].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, at least 13 million donors were deferred due to having the risk of infection that could be transmitted through blood, a preexisting medical disease or anemia 3. Due to this, blood donor selection is a cornerstone for blood transfusion safety, designed to safeguard the health of both donors and recipients 4. Blood donor eligibility is determined by medical interview, based on national guidelines for donor selection 5…”
Section: Introductionmentioning
confidence: 99%